Subdural Hemorrhage as an Early Presentation in a Case of Sotos Syndrome - Nomakuchi, Tomoki T.; Alves, Cesar Augusto P.; Beslow, Lauren A.; Zarnow, Deborah; Goyal, Neera; Zackai, Elaine H.; Reynoso Santos, Francis Jeshira (Neuropediatrics, 2023)
Subdural hemorrhages (SDHs) in the pediatric population are associated with a high mortality and morbidity and may present in the context of abusive head trauma. Diagnostic investigations for such cases often include evaluation for rare genetic and metabolic disorders that can have associated SDH. Sotos syndrome is an overgrowth syndrome associated with macrocephaly and increased subarachnoid spaces and rarely with neurovascular complications. Here, we report two cases of Sotos syndrome, one with SDH during infancy who underwent repeated evaluation for suspected child abuse prior to the Sotos syndrome diagnosis and the other with enlarged extra-axial cerebrospinal fluid spaces, demonstrating a possible mechanism for SDH development in this setting. These cases suggest that some individuals with Sotos syndrome may be at elevated risk of developing SDH in infancy and that Sotos syndrome should be on the differential diagnosis during a medical genetics evaluation in cases of unexplained SDH, especially in the setting of macrocephaly.
Keywords: subdural hemorrhage; Sotos syndrome; NSD1